(untitled) (Research, Society and Development, 2022)
Polyethylene terephthalate (PET) has become one of the most used plastic materials worldwide owing to its versatility and low production costs. However, environmental issues arise from the inadequate disposal of this material and the considerable volume it occupies in sanitary landfills, particularly because the long decomposition time of PET. Considering this scenario, the construction industry has a considerable potential to incorporate wastes from other productive systems. In this regard, concrete and mortar can be an alternative to incorporate PET. Thus, this study aimed to evaluate the mechanical properties of mortars produced with a partial replacement of fine aggregate by crushed PET. Two mix designs with different binder/ fine aggregate ratios were produced using Portland cement CP II Z-32, lime, sand, and crushed PET replacing 5%, 10%, 15%, 20%, and 25% of sand. The compressive strength and splitting tensile strength were determined. As a result, it was observed that both compressive and splitting tensile strength values increased with increasing PET percentages from the age of 14 days. These results indicate that the use of PET replacing the conventional fine aggregate can improve the mechanical properties of mortars.